ANALISIS KAJIAN POTENSI EKONOMI WILAYAH KABUPATEN AGAM - Azizatul Jannah; Tri Kurniawati (Universitas Negeri Padang, 2018)
The purpose of this research is to find out the besic sector that has fast growth in region Kabupaten Agam. This research is descriptive quantitative research with the method is location quotient analysi, shift share analysi. This research is using sekunder data from PDRB Kabupaten Agam and PDRB Sumatera Barat Province with the permanen price in year 2010 from 2012-2016. Based on the location quotient analysis. The risult showed that there were four sector basic. Sector agrikultural, forestry, fishery, industrial processing, large trade, retail, car and bike repaired, education service. Based on the Shift Share analysis, sectors that have a fast growth rate are forestry and fisheries agriculture, mining and quarrying, construction, large trade, retail, car and bike repaired, transportation and warehousing, information and communication, government administration, mandatory defense and social security , education services, health services and social activities. Keyword: Base Sector, Location Quotient (LQ) analysis, Shift Share analysis